Pengaruh digital perpajakan dan self-assessment system terhadap perilaku tax avoidance pada usaha kecil menengah di Jalan Flamboyan Manado - Kakunsi, Indy Maria; Kalangi, Lintje; Wangkar, Anneke (Riset Akuntansi dan Portofolio Investasi, 2025)
This study examines the influence of digital taxation and the self-assessment system on tax avoidance behavior among Small and Medium Enterprises (SMEs) in Indonesia. The research is motivated by the persistent issue of low tax compliance in the SME sector despite the government’s implementation of tax digitalization and the self-assessment system. A quantitative approach was employed using a sample of 71 SME taxpayers operating on Flamboyan Street, Manado, North Sulawesi, selected through simple random sampling. Primary data were collected via an online questionnaire (Google Forms). The data were analyzed using multiple linear regression and t-tests, supported by classical assumption tests to ensure the validity of the regression model. The findings reveal that digital taxation has a significant negative effect on tax avoidance behavior, indicating that improved implementation of digital tax systems enhances transparency and oversight, thereby reducing opportunities for tax avoidance. Conversely, the self-assessment system has a significant positive effect on tax avoidance behavior, suggesting that greater autonomy in calculating, paying, and reporting tax obligations increases the likelihood of exploiting legal loopholes.The study concludes that while digital taxation effectively curbs tax avoidance among SME taxpayers, the self-assessment system must be accompanied by stronger oversight and enforcement mechanisms to prevent misuse. These results provide policy insights for strengthening tax compliance in Indonesia’s SME sector.